Pseudomonas fluorescens and Trichoderma viride enriched bioconsortium for the management of Fusarium wilt in carnation and gerbera under protected cultivation - V. JEGADEESWARI, V. P. SANTHI and N. SELVARAJ, LINGAN RAJENDRAN*, P. RAJA, (Indian Phytopathology, 2014)
The talc-based formulation of two bioagents (Pf1 and Tv) and its mixture were tested against Fusarium wilt in carnation and gerbera under protected cultivation. The application of talc-formulation through rooted cutting as dipping, soil application and foliar spray significantly reduced the wilt incidence under protected conditions. The mixture of two biocontrol agents performed better than the individual agent. Among the different treatments tested, Pf1 + Tv (as seedling dip + soil application enriched with FYM + foliar spray @ monthly interval) recorded the disease incidence of 7.8 per cent in carnation and 3.3 per cent in gerbera in the first year whereas the disease incidence was 9.5 per cent in carnation and 7.0 per cent in gerbera in the second year which was at par with carbendazim treatment. Simultaneously, when compared to chemical treatment, the stem length and number of flowers of carnation (86.0 cm and 47.5 per m2) and spike length, number of flowers of gerbera (65.6 cm and 38.0 per m2) were maximum in beds treated with Pf1 + Tv (seedling dip + soil application enriched with FYM + foliar spray @ monthly interval) followed by individual bioagent application.